The Development Of COVID-19 Treatment Regimen (Article Review ) - Hussein, Rdhwan M.; Mohammed, Zainab Sajid; AL-Fatlawy, Hawraa Natiq Kabroot; Hamza Al-Kraity, Asst.Prof.Dr. Wijdan Rajh (Medical Science Journal for Advance Research, 2023)
Background: Since December 2019, a new human coronavirus outbreak has spread across various nations, causing numerous cases and deaths. COVID-19 is a disease caused by the brand-new SARS-CoV-2 virus (a brand-new stress of coronavirus). Wuhan, Hubei Province, People’s Republic of China, is a ten-million-person metropolis. The cornerstone and most important management strategy for clinical management of COVID-19 remains early adjunct care and monitoring, which includes O2 supplementation, organ support, and interference of complications, particularly acute respiratory distress syndrome, organ failure, and secondary health facility infections. Conclusion: COVID-19 is a pandemic that is causing an increase in the number of infections and deaths. In response to the epidemic, many pharmacologic medicines are being utilized off-label or evaluated for therapy around the world. Antiviral medications (eight drugs), antimalarial drugs (two drugs), systemic corticosteroids (five drugs), and immune-based therapy are the four primary groups of drugs suggested in treatment guidelines around the world (seven drugs). There is a lot of difference between these rules in general. These mostly dealt with drug indications, types of pharmaceuticals, dose regimens, treatment periods, and drug safety in various patient groups